2010
DOI: 10.1111/j.1872-034x.2009.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel biomarker for oxidative stress induced by hydrogen peroxide in primary human hepatocytes using the 2‐nitrobenzenesulfenyl chloride isotope labeling method

Abstract: The NBS labeling technique was useful to identify biomarkers. Serum MnSOD may be a useful biomarker that can distinguish between SS and NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Previous experiments showed that the expression of MnSOD was decreased when retinal ganglion cells were treated with hydrogen peroxide ( Khan et al, 2012 ). However, in primary hepatocytes and human macrophages, the expression of MnSOD was increased when the cells were treated with hydrogen peroxide ( Kinscherf et al, 1998 ; Takami et al, 2010 ). Also, no significant change of MnSOD was observed when pancreatic beta cells were treated with hydrogen peroxide ( Kimoto et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments showed that the expression of MnSOD was decreased when retinal ganglion cells were treated with hydrogen peroxide ( Khan et al, 2012 ). However, in primary hepatocytes and human macrophages, the expression of MnSOD was increased when the cells were treated with hydrogen peroxide ( Kinscherf et al, 1998 ; Takami et al, 2010 ). Also, no significant change of MnSOD was observed when pancreatic beta cells were treated with hydrogen peroxide ( Kimoto et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of cytokeratin 18 fragment [94], adiponectin [95], high sensitivity CRP [96], thioredoxin [97], and MnSOD [98] are useful for diagnosis of NASH. In a large-scale study, cytokeratin 18 fragment was shown to a useful single diagnostic marker for NASH [99].…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Takami Y. et al . (2010) showed that systemic MnSOD protein is significantly higher in NASH patients than in steatotic patients and healthy controls [ 98 ]. A case–control and intra-familial allele association studies prove the evidence that carriage of the rs4880 polymorphism involved in determining the susceptibility to oxidative stress and fibrogenesis, respectively, have been associated with the severity of liver fibrosis in adults and children with NAFLD [ 99 ].…”
Section: Manganese Superoxide Dismutase Gene ( Mnsod mentioning
confidence: 99%